ISH ADA-06 INTIMA-MEDIA THICKNESS OF THE CAROTID BULB IS ASSOCIATED WITH WORSENING OF ORTHOSTATIC HYPOTENSION IN PATIENTS WITH METABOLIC DISORDER. (September 2016) - Kobayashi, Yusuke; Kobayashi, Hideo; Ishiguro, Hiroaki; Yatsu, Keisuke; Fujikawa, Tetsuya; Umemura, Satoshi
Abstract : Objective: Though both carotid bulb and aortic arch are known to play important roles in regulation of blood pressure through modulation in baroreflex function, few studies have investigated the association of carotid bulb atherosclerosis and large arterial stiffness and orthostatic blood pressure change. Design and Method: Patients with metabolic disorder such as hypertension, dyslipidemia and diabetes mellitus underwent measurement of segment-specific carotid intima-media thickness (IMT) (as an index of atherosclerosis of carotid bulb), cardio-ankle vascular index (CAVI) (as an index for large arterial stiffness), heart rate variability (HRV) (as an index of baroreflex function) and sit-to-stand orthostatic blood pressure change (as a simple method for detecting orthostatic hypotension). Results: Of the 129 patients, mean age was 65.7 years and 32.6% were male. Hypertension, dyslipidemia and diabetes mellitus were diagnosed in 64.3%, 87.6% and 7.8% of the patients, respectively. Common carotid artery (CCA) IMT and carotid bulb IMT and internal carotid artery (ICA) IMT had significant positive correlation with CAVI (R = 0.349, P < 0.001; R = 0.364, P < 0.001; R = 0.186, 0.035; respectively). Carotid bulb IMT and ICA IMT had significant negative correlation with high frequency (HF) component of HRV parameter (R = -0.183, P = 0.038; R = -0.213, P = 0.015; respectively), whereas CCA IMT had no correlation with HF. Only carotid bulb IMT had significant negative correlation with orthostatic systolic blood pressure (SBP) change (R = -0.211, P = 0.016). In multivariable analysis using stepwise method, carotid bulb IMT had significant negative correlation with orthostatic SBP change (β=-0.194, P = 0.022), adjusted for variables. Conclusions: Atherosclerosis of the carotid bulb was involved in the severity of orthostatic hypotension. Although possibility of the mechanism was thought to be stiffening of large arteries and baroreceptor dysfunction, further study is needed to evaluate the mechanism.